Strategy Formulation and Implementation of Goraka Network - Andries, Patrick Marco; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2014)
Abstract. The rapid growth of Internet nowadays began to shift the behavior of people accessing information and also the way people of socialize and communicate. The fast changing of people behavior due to the impact of rapid Internet development open a new opportunity to Software House Industry. They were able compete into new market that rapidly growth everyday by utilizing the Web Technology. Goraka Network (GNET) is a one of Software House, in Bandung. Specialized in developed Web based Software and Information Technology Consulting, as the opportunity grows their competitor began to seek similar market with them and produces a fierce competition among software house industry in Bandung. GNET are needed formulate their business strategy comprehensively in order to survive and win the competition in their market segment.To formulate their strategy firstly they were needed to explore their business issue, it can be done by external and internal analysis, external analysis state that there are major issue due to the high software piracy rate in Indonesia and the high rivalry rate among the competitor which resulted fierce competition. In order to win the competition GNET are needed to innovate and give more value to their customer but in other hand external analysis suggest that GNET are still needed to fix their weaknesses which were lack of marketing effort and the unstable revenue due to lack of project they can handled which potentially become an serious problem in the future.Based on external and internal analysis the strategy formulation are made consisting of directional strategy which is stated that GNET were in growth position and needed to focus on horizontal growth by creating new line of services in order to survive from the high rivalry among their competitors, it can be done by utilizing differentiation strategy which also used to anticipate the high software piracy rate in Indonesia. Differentiation will given GNET an unique value for their potential customer that prefer to use pirated software so they may shift to use GNET software. The differentiation strategy can be done by focused at research and development strategies as the foundation of product innovation, but turn out that GNET are needed to create new Small Business Unit (SBU) to support them to provide new services while they focus to improve their own services value toward their customer and overcome their weaknesses that described by the internal analysis.All of the plan of GNET and its new SBU are described as functional strategies, and each of their functional strategy were mapped into implementation plan that consist of budget, timeline and action plan for three years with the milestone for each strategies, the strategies majorly consist of research and marketing strategies. At research GNET were focus at Research of new module of Software while their SBU focused at Research of new kind of Web Product to target specific market niche, each time of research conducted they were expected to produce one kind web product or one kind of software module. In Marketing they shares similar marketing strategies which used online promotion tool via website and social media and offline promotion media using brochure and newspaper this strategy aims for specific numbers of customer each year. By applied the functional strategies both of GNET and its SBU were projected to yield a positive number Economic Value Added and positive revenue projection for three years.Keywords: Software House, Services, Fierce Competition, Business Strategy